2018
DOI: 10.1002/slct.201702543
|View full text |Cite
|
Sign up to set email alerts
|

pEDOT:Vitamin K1 Composites: An Electrochemical Study on Stable, Water‐Permeable, Proton‐Bonding Thin‐Film Electrodes

Abstract: Herein we report detailed electrochemical studies of a conducting polymer composite that is engineered to selectively react with protons and that has reactive sites across the entirety of the volume due to the excellent water permeability throughout the film. This chemically modified electrode (CME) utilises a conducting polymer as the source of charge carrier and Vitamin‐K as the water‐insoluble redox species that bonds protons in reduction and releases protons in oxidation. The overall number of active proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Instead of a hydroxy group, its structure includes a methyl group in the 3‐position and a side chain of variable length in the 2‐position. The synthetic provitamin menadione, without this side chain (Figure ), has been presented as anode material for potassium‐ion batteries, with a surprisingly low redox potential in the range of 1 V vs. K + /K and hence approximately 1.2 V lower than in lawsone and juglone (other studies showed redox activity of vitamin K in the range of −0.3 V vs. Ag/AgCl) . Charge storage in the range of 220 mAh g −1 after 100 cycles at 100 mA g −1 was presented as a combination of redox activity of menadione and significant contributions of graphene nanotubes used for immobilization and acetylene black used as conductive additive.…”
Section: Electrodesmentioning
confidence: 99%
“…Instead of a hydroxy group, its structure includes a methyl group in the 3‐position and a side chain of variable length in the 2‐position. The synthetic provitamin menadione, without this side chain (Figure ), has been presented as anode material for potassium‐ion batteries, with a surprisingly low redox potential in the range of 1 V vs. K + /K and hence approximately 1.2 V lower than in lawsone and juglone (other studies showed redox activity of vitamin K in the range of −0.3 V vs. Ag/AgCl) . Charge storage in the range of 220 mAh g −1 after 100 cycles at 100 mA g −1 was presented as a combination of redox activity of menadione and significant contributions of graphene nanotubes used for immobilization and acetylene black used as conductive additive.…”
Section: Electrodesmentioning
confidence: 99%
“…In this reaction, UQH 2 is oxidized through a partially reduced intermediate ubisemiquinone (UQH * ) back to UQ. [2,3] However, once oxidized, the UQ form must be reduced by antioxidant enzymes such as NAD(P)H quinone oxidoreductase NQO1 or Cytochrome B5 reductase to be reduced again and have the capacity to transfer electrons. [4] CoQ10 is a highly studied nutrient whose biochemical and physiological role in the human body has been already relatively well established.…”
Section: Introductionmentioning
confidence: 99%
“…Chemically modified electrodes (CMEs), which have prospects for various applications, [1][2][3][4] are of great research interest in the fields of electrochemistry and electroanalytical chemistry. The fabricated Nafion/Mb/AuNRs/CILE was used as an electrochemical biosensor for determining trichloroacetic acid (TCA) and sodium nitrite (NaNO 2 ).…”
mentioning
confidence: 99%
“…Low detection limits and wide linear ranges were obtained in electrocatalytic investigations of different catalytic substrates including TCA and NaNO 2 , which exhibited potential applications in actual sample detection. Chemically modified electrodes (CMEs), which have prospects for various applications, [1][2][3][4] are of great research interest in the fields of electrochemistry and electroanalytical chemistry. As a kind of frequently used redox protein, myoglobin (Mb) has the physiological functions of oxygen storage and transportation with its three-dimensional structure system shown in Scheme 1.…”
mentioning
confidence: 99%